Evaluating Covid-19 publications for sex and gender-specific health content: A bibliometric analysis - Abigail Oyasu; Aysha Salter-Volz; Chen Yeh; Lutfiyya N. Muhammad; Reshma Jagsi; Nicole C. Woitowich (PLoS ONE, 2025)
Background Sex and gender are key variables which inform human health and disease. It remained unclear how sex and gender were considered, evaluated, reported, or analyzed within Covid-19 research. This article evaluates the proportion of Covid-19-related articles which highlighted sex- or gender-specific health content and examines associations with author gender. Materials and methods Article records for 134,008 publications indexed in the LitCovid database were extracted on June 1st, 2021. Metadata such as publication year, author names, and country of institutional affiliation were obtained from Elsevier’s SCOPUS database by matching PubMed Identifiers (PMIDs). Only articles with matching SCOPUS records were included in the study, resulting in a final sample of 94,488 articles. First and last author gender was assigned to a subset of 71,597 articles. Article title, abstracts, and keywords were screened for sex or gender-specific health content using a text-based search strategy. Descriptive statistics and regression analyses were used to study associations between author gender and the presence or absence of sex or gender-related health content. Results Only 4% of Covid-19-related articles highlighted sex or gender-related health content. Papers with women first authors were more likely to highlight sex or gender-related health content compared to papers with men as first authors (4.15% n = 1,339 vs 3.68%, n = 1,997) [X2 (1, n = 86,468) = 12,01, p = 0.0005]. Papers with women first and last authors had an increased probability of addressing sex or gender-related health with an odds ratio of 1.16 (95% CI 1.04 – 1.29). While there was no association between author gender and journal impact, articles which highlighted sex or gender-related health content were published in journals with higher CiteScores [Mdn = 5.0, Q1-Q3 (3.5–8.2) vs. Mdn = 4.7, Q1-Q3 (2.8–8.0)]. Conclusions The paucity of publications to highlight sex or gender in the context of the Covid-19 pandemic is alarming. Research that focuses on the influence of sex and or gender is essential for advancing the scientific understanding of disease processes.